Oyster Mushroom: Biochemical and Medicinal Prospects (Bangladesh Journal of Medical Biochemistry, 2013)
Mushroom possesses a vital portion of fungal kingdom creating a huge diversity. As a food major portion of these are unfit but as a whole these play an important role to maintain a sound health. Among them some are used as food and some as medicine. Many unknown mysterious components, very much needed for homeostasis of human body, are present in mushroom, which are now recognized as important area for biomedical researches. Oyster mushroom (Pleurotus ostreatus) is such a mushroom which is used both as food and medicine to ensure the fitness of body. It contains protein, carbohydrates, fat, fiber, water, different kinds of vitamins and minerals as well as secondary metabolites. Its statins are outstanding in decreasing the harmful plasma lipids and in reducing blood pressure thereby reducing the risk of cardiovascular diseases. The beta-glucan component of oyster stimulates the immune system of the body. This mushroom is also found to be effective and beneficial in diabetes, cancer, microbial infections and so on. However, there are many other life saving components in oyster mushroom whose nature, effectiveness and mode of actions are yet to be characterized and defined.These valuable unknown informations are now subjects of researches. Bangladesh, like other countries of the world is conducting such type of researches but still has to go a long way in this field. At this very moment, it can be said beyond any doubt that oyster mushroom is very good as an alternative food and as a medicine. DOI: http://dx.doi.org/10.3329/bjmb.v3i1.13804 Bangladesh J Med Biochem 2010; 3(2): 23-28